PENGARUH FINANCIAL DISTRESS, ASIMETRI INFORMASI, TIPE AUDITOR, DAN MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP PRUDENCE AKUNTANSI - Maria Emilia Carolline; Dian Purnama Sari (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2023)
This study aims to examine and analyze the effect of financial distress, information asymmetry, auditor type and good corporate governance mechanism on accounting prudence. Data collection in this study was carried out by indirect observation by researchers on the research object, namely manufacturing companies listed on the Indonesia Stock Exchange, to be precise at the Capital Market Reference Center. Observations made by researchers are non-participant observations, where the authors make observations as data collectors without involving themselves or being part of the social environment being observed, in this case the manufacturing companies and the listed components. The results of this study indicate that financial distress has a positive effect because when a company's finances are in trouble, managers tend to apply prudent accounting principles to reduce conflicts between investors and creditors, meaning that managers will increase their understanding of accounting prudence in response to high levels of financial distress. Information asymmetry has no effect, meaning that whether there is information asymmetry between investors and company management will not affect management's ability to prepare prudential financial reports. The type of auditor has a positive effect because the big four will be better able to detect possible errors in financial statements so that companies will apply accounting prudence more. The board of commissioners has no effect, because the management oversight function is not carried out properly because not all commissioners are able to carry out their duties properly. The independence of the board of commissioners has no effect, because an independent board of commissioners does not necessarily reduce conflicts of interest in a company because not all commissioners are free from business relationships.